PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN KETIDAKPUASAN MASYARAKAT KOTA SOLO SEBAGAI KOTA LAYAK ANAK - Ariefah Yulandari; Waluyo Budi Atmoko (JANACITTA, 2022)
Solo City is one of the cities for observing children. This is evidenced by the changes and achievements of the City of Solo as a Child-friendly City. Implementation of Presidential Regulation Number 25 of 2021 concerning Child Friendly Regency/City Policies, with the Law on assisting Child Friendly Cities which has 6 main indicators (institutional, basic health and welfare, civil rights and freedoms, family environment and alternative care, special protection, and education, use of leisure time and cultural activities) with 24 sub-indicators making progress in the process of achieving Child Friendly Cities certainly has value that is felt by the community. A service quality is said to be successful if the value of satisfaction is higher than the value of dissatisfaction. This study aims to examine the service quality variable in the City of Solo in implementing the Child Friendly City program. By using a service quality model that includes 5 spaces, a simple research model concept and using a simple regression analysis hypothesis testing in this study, the results obtained indicate that the satisfaction value is lower than the dissatisfaction value. This study found that there were things that were missed during the service quality process so that community satisfaction had a low value. What is expected by the community is not in accordance with the expected reality. So that these results provide an indication that the achievement of service quality in Solo City as a Child Friendly City has not been categorized as a maximum service quality even though all forms of processes have been carried out to implement Solo City as a Child Friendly City according to the indicators.